ANALISIS TINGKAT KEBERDAYAAN KELUARGA MASYARAKAT PEDESAAN DAN PERKOTAAN - Astriana Baiti; Era Purike (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Based on data from the Directorate General of Population and Civil Registration (Dukcapil) of the Ministry of Home Affairs (Kemendagri), there are 3.97 million residents who are married and divorced until the end of June 2021. This number is equivalent to 1.46% of the total population of Indonesia, which reached 272.29 million people. The family is seen as an easily broken institution, so it needs to be protected. The family certainly cannot inhibit the influence of other environments on the family environment. It takes the ability to manage all the resources that exist inside and outside the family to overcome family problems, which can protect the family from rupture. Therefore, the effectiveness of implementing family functions is expected to determine significantly family empowerment. The research method uses a quantitative survey method using a questionnaire instrument. The study was conducted in two sub-districts, namely Duren Sawit District as an illustration of urban areas and Jasinga District as an illustration of rural areas. The results showed that the level of empowerment in rural and urban communities was not good because most respondents (47.1% urban communities, 49.3% rural communities) were in the moderate empowerment category.